PERANCANGAN DAN PENGUJIAN UNJUK KERJA SISTEM MONITORING KADAR LENGAS BERBASIS GYPSUM BLOCK UNTUK MEMANTAU DINAMIKA TANAH POLIETILEN, POLISTIREN DAN OTHER - Agung Prasetyo; Eka Firmansyah; Lilik Sutiarso (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2016)
Soil moisture sensor (moisture content) is very important in determining the time a crop irrigation, soil wetting depth, the depth of the growth of plant roots and soil wetting sufficiency. This study discusses the design and implementation of the system of measuring soil moisture content of gypsum block based electronic. Measurement data are stored automatically in a database and then performed with a sensor calibration step gravimetric measurement results. The test results demonstrate system performance design performance measurement system with accuracy (%) error rate. Then used to determine gypsum block sensors with good performance